2011
DOI: 10.1101/gr.122218.111
|View full text |Cite
|
Sign up to set email alerts
|

Parallel evolution of transcriptome architecture during genome reorganization

Abstract: Assembly of genes into operons is generally viewed as an important process during the continual adaptation of microbes to changing environmental challenges. However, the genome reorganization events that drive this process are also the roots of instability for existing operons. We have determined that there exists a statistically significant trend that correlates the proportion of genes encoded in operons in archaea to their phylogenetic lineage. We have further characterized how microbes deal with operon inst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
62
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 53 publications
(63 citation statements)
references
References 94 publications
1
62
0
Order By: Relevance
“…To evaluate the effect of polarity on the functional categorization of genes, the EI of genes in the 209 operons previously identified in M. maripaludis S2 were examined (9). If the insertion of the Tn5 transposon interrupts transcript, genes upstream of a possibly essential gene will always appear possibly essential.…”
Section: Resultsmentioning
confidence: 99%
“…To evaluate the effect of polarity on the functional categorization of genes, the EI of genes in the 209 operons previously identified in M. maripaludis S2 were examined (9). If the insertion of the Tn5 transposon interrupts transcript, genes upstream of a possibly essential gene will always appear possibly essential.…”
Section: Resultsmentioning
confidence: 99%
“…The MW56 strain contained the SP1 operon between convergently transcribed genes (encoded by loci PF0574 and PF0575; Figs. S2 and S3) within a ∼100-bp region having little to no transcriptional activity, according to a previous tiling array study of P. furiosus (22). The P. furiosus strains used here are summarized in Table S1.…”
Section: Resultsmentioning
confidence: 99%
“…Extensive studies of the transcriptome (Hendrickson et al 2007 and proteome (Xia et al , 2009 showed that genes of the methanogenic pathway are significantly regulated by H 2 . Our recent study on the transcriptome map of M. maripaludis generated a comprehensive list of protein-coding and noncoding RNAs for systems modeling of this organism (Yoon et al 2011).…”
mentioning
confidence: 99%
“…First, we generated a comprehensive list of coding and noncoding RNAs through comparative analysis of the complete transcriptome and a comprehensive PeptideAtlas (Deutsch 2010) for M. maripaludisi.e., genome-wide alignments of a collection of peptides that were experimentally detected across a diverse set of tandem mass spectrometry experiments (Yoon et al 2011;Supplemental Methods). Next, we generated a compendium of over 50 transcriptome profiles from steady-state conditions and during dynamic cellular response to a spectrum of environmental perturbations.…”
mentioning
confidence: 99%
See 1 more Smart Citation